(RETRACTED) THE ACTUALIZATION LITERATURE BASED LEARNING VERBAL-LINGUISTIC INTELLIGENCE - Nur Ihsan Halil (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2017)
Retraction NoticeLeksika, Vol.11, No.1, February 2017Purwokerto, January 13, 2021  First Published Feb, 2017  Article Information Original Article:http://jurnalnasional.ump.ac.id/index.php/LEKSIKA/article/view/7374 AbstractAt the request of the Author, the following article has been retracted:Halil, N. Ihsan. 2017. The actualization literature based learning verbal-linguistic intelligence. Leksika Vol. 11, No.2, February 2017. Purwokerto: Faculty of Letters, Universitas Muhammadiyah Purwokerto.Due to some lack of coordination with the corresponding author, the article had been managed to have a double publication. On behalf of Leksika, I send my deep apology to the author and our readers.Thank you,Best regards, KhristiantoEditor-in-ChiefLeksika: Jurnal bahasa , sastra dan pengajarannya.